A stable Maximum-Entropy Meshless method for analysis of porous media. (December 2016) - Nazem, M.; Kardani, M.; Bienen, B.; Cassidy, M.
Abstract: Consolidation analysis of saturated porous media demands the coupling of solid displacements with the pore fluid pressure via the equilibrium and the continuity of mass. In this paper, a stable numerical procedure is presented for coupled analysis of consolidation problems in geotechnical engineering. The numerical framework is based on the Element-Free Galerkin method and the principle of Maximum Entropy. Identical shape functions are employed for approximating the displacement field as well as the pore fluid pressure field. The proposed method is used for analysing several consolidation problems assuming elastic and elastoplastic soil behaviour. The numerical results indicate that the proposed Maximum-Entropy Meshless method based on the maximum entropy shape functions is able to provide stable and robust solutions for consolidation problems in porous media.